Deaf and refugee – a different situation - Olsen, Elisabet Trengereid (Border Crossing, 2018)
This article elaborates on the subject; Deaf and refugee - a different situation, and is based on theoretical- and empirical material collected for the master thesis Mediated Interaction. The thesis’ data was collected by focus group interviews, answering the following research question: What do interpreters do when they interpret between deaf and hearing people? - with emphasis on deaf immigrants. With information about Deaf People and Sign Language as a backdraft, the article aims to describe the situation for deaf refugees in Norway. The focus is on access to communication, and how elements such as trust, cultural differences and continuous language barriers influence interpreted situations and deaf refugees’ inclusion into society. Findings show that language is the key to autonomy in a new land. In this process, the national Deaf Community plays an important role for deaf refugees. In addition, do both hearing and deaf interpreters reduce language barriers? In this process, they need flexibility when facilitating communication between hearing- and deaf interlocutors